Characterization of gel polymer electrolytes for lithium oxygen batteries / Mohd Zieauddin Kufian - Mohd Zieauddin , Kufian (2021)
Gel polymer electrolytes (GPEs) based on poly(methyl methacrylate) (PMMA) are developed. Lithium-ions donor which are lithium bis(oxalato)borate (LiBOB) and lithium bis(trifluoromethanesulfonyl)imide (LiTFSI) and tetraethylene glycol dimethyl ether (TEGDME) solvent was used in this work. Three GPE systems were prepared i.e. PMMA-LiBOB-TEGDME, PMMA-LiTFSI-TEGDME and PMMA-LiTFSI-TEGDMECalix[ 6]arene. Calix[6]arene as a trapping agent for anions is only added in 28.85wt.% PMMA–25wt.% LiTFSI–46.15wt.% TEGDME GPE (B4 sample) due to the highest electrolyte conductivity of (2.80±0.01) mS cm-1 obtained compared to 32.96wt.% PMMA–15wt.% LiBOB–52.04wt.% TEGDME GPE (A2 sample) of (1.69±0.09) mS cm-1. Addition of Calix[6]arene in B4 sample decreased the electrolyte conductivity. From Fourier-transform infrared (FTIR) studies, complexation between Li+ ions and functional groups of (C=O), (O-CH3) and (C-O-C) corresponding to PMMA and (C-O) corresponding to TEGDME have occurred. Addition of Calix[6]arene in B4 sample shows the occurrence of interaction between fluorine atom from CF3 group corresponding to TFSI¯ anion with H+ ion from OH group of calix[6]arene. Transference number measurement shows the electrolyte containing 0.5wt.% Calix[6]arene in B4 sample (now known as sample C1) gives highest lithium-ion transference number, Lit  of 0.51. Electrochemical window stability is most stable up to 5.5 V for sample A2. Sample C1 provides excellent stability at electrode-electrolyte interface and higher discharge capacity (1.40 mAh cm-2 or 0.53 mAh) along with discharge capacity retention of 35% after fifth cycles when applied in lithium-oxygen battery.